Faktor Somatogenik, Psikogenik, Sosiogenik yang Merupakan Faktor Risiko Kejadian Skizofrenia Usia < 25 Tahun (Studi di Kecamatan Kepil Kabupaten Wonosobo) - Dhian Ika Prihananto; Suharyo Hadisaputro; Mateus Sakundarno Adi (Jurnal Epidemiologi Kesehatan Komunitas, 2018)
Background: Schizophrenia is a clinical syndrom of several disturbing psichological condition, involving process of thinking, emotion, perception, and attitude. Risks factors contributing to the appearance of schizophrenia <25 years old are factors of somatogenic, psychogenic, and sociogenic. The aim of the reaearch was to povide evidence that factors of somatogenic, psychogenic, and sociogenic are contributing factors to schizophrenia <25 years old.Methods: This research is a research of mix method, design of case-control study reinforced by indepht interview. The population of study was people with schizophrenia <25 years old in Kepil Subdistrict, Wonosobo Regency. The sample consisted of 55 cases and 55 controls based on consecutive samplung. The research instrument was guided interview. Data were then analyzed using chi square (univariate, bivariate) and logistic regression (multivariate).Result: Contributing factors to risk factors of schizophrenia observed on people <25 years old are family with schizophrenia (OR=8,016; 95%CI=2,342-27,433; p=0,001), bad temper (OR=3,223; 95%CI=1,159-8,961; p=0,025), early deprivation (OR=5,356; 95%CI=1,180-24,309; p=0,030), experiencing stress (OR=5,451; 95%CI=1,739-17,083; p=0,004), low social development (OR=3,363; 95%CI=1,072-10,552; p=0,038), low economic condition (OR=5,294; 95%CI=1,696-16,524; p=0,004).Conclusion: Somatogenic factor that proved to be a risk factor for schizophrenia <25 years old is having a family history of schizophrenia, has a bad temper. Psychogenic factors are experiencing early deprivation, experiencing stress. Sociogenic factor is bad social development, low economic level.